The three moments of skin cream application: an evidence-based proposal for use of skin creams in the prevention of irritant contact dermatitis in the workplace - Hines, John; Diepgen, Thomas L. (Journal of the European Academy of Dermatology and Venereology, 2017)
Contact dermatitis is one of the most common occupational diseases, with serious impact on quality of life, lost days at work and a condition that may be chronically relapsing. Regular prophylactic skin cream application is widely acknowledged to be an effective prevention strategy against occupational contact dermatitis; however, compliance rates remain low. To present a simple programme for skin cream application in the workplace with focus on implementation to drive down the rate of occupational irritant contact dermatitis, an expert panel of eight international dermatologists combined personal experience with extensive literature review. The recommendations are based on clinical experience as supported by evidence-based data from interventional studies. The authors identified three moments for skin cream application in the work place: (i) before starting a work period; (ii) after washing hands; and (iii) after work. Affecting behaviour change requires systematic communications, monitoring and reporting, which is proposed through Kotter's principles of organizational change management. Measurement tools are provided in the appendix. Interventional data based on application of this proposal is required to demonstrate its effectiveness.
Gesehen am 10.07.2018
First published: 22 August 2016